1965
DOI: 10.1021/jf60140a011
|View full text |Cite
|
Sign up to set email alerts
|

Defoliant Residues, Determination of Cyanamide Residues on Ginned Cottonseed

Abstract: translocated into the terminal buds and subtending internodes in amounts that inhibited terminal bud growth and induced internodal abscission. During the development of these responses, the lateral buds apparently did not absorb sufficient A'-(3-nitro-l -naphthyl)phthalamic and Ar-(5 -acenaphthenyl) phthalamic acids at the dosage levels used to inhibit their subsequent growth. It is probable that any residual amounts of these compounds became inactive during this period as far as growth inhibition was concerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The enzyme (0.05-0.2 units) was incubated with 20mM cyanamide in 5 mM sodium phosphate buffer (pH 7.7) (total volume = 0.25 ml) at 37°C for 15-60 min, depending on the activity of the enzyme. The cyanamide concentration was determined by a colorometric assay at 530 nm in 20 Al of the incubation mixture before and after enzyme addition (8) (17), the end-product biuret does not interfere], urea (17), formylcyanamide and acetylcyanamide (formation of the corresponding substituted urea, measured by the decrease of the absorption at 250 nm).…”
mentioning
confidence: 99%
“…The enzyme (0.05-0.2 units) was incubated with 20mM cyanamide in 5 mM sodium phosphate buffer (pH 7.7) (total volume = 0.25 ml) at 37°C for 15-60 min, depending on the activity of the enzyme. The cyanamide concentration was determined by a colorometric assay at 530 nm in 20 Al of the incubation mixture before and after enzyme addition (8) (17), the end-product biuret does not interfere], urea (17), formylcyanamide and acetylcyanamide (formation of the corresponding substituted urea, measured by the decrease of the absorption at 250 nm).…”
mentioning
confidence: 99%
“…The initial CAH enzymatic activity was determined by measuring the consumption of cyanamide after incubation with CAH for 15-60 min, followed by a colorimetric assay at 530 nm (32). It was reported that A 530 nm absorption is linear with cyanamide concentrations only up to 200 M (33), but in our hands the linear relationship can be extended up to 5 mM cyanamide (Fig.…”
Section: Ddi2/3 Encodes a Member Of The Hd Domain Family Ofmentioning
confidence: 56%
“…The solution was incubated for 10 min at room temperature in the dark. Absorbance at 530 nm (Steller et al, 1965) was measured to detect reduced cyanamide concentration indicative of the presence of cyanamide hydratase.…”
Section: Methodsmentioning
confidence: 99%